2023
DOI: 10.3390/molecules28020581
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-l-phenylalanine Racemization during TBTU Amidation: An In-Depth Study for the Synthesis of Anti-Inflammatory 2-(N-Acetyl)-l-phenylalanylamido-2-deoxy-d-glucose (NAPA)

Abstract: A thorough study on the amidation conditions of N-acetyl-l-phenylalanine using TBTU and various bases is reported for the synthesis of 2-(N-acetyl)-l-phenylalanylamido-2-deoxy-d-glucose (NAPA), a promising drug for the treatment of joints diseases. TBTU-mediated diastereoselective amidation reaction with 1,3,4,6-tetra-O-acetyl-β-d-glucosamine always gave racemization of N-acetyl-l-phenylalanine. The stereochemical retention under amidation conditions was studied in detail in the presence of difference bases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Although phenylalanine is not known for its susceptibility to racemization, like e.g., phenylglycine containing peptides, literature shows that phenylalanine racemization can occur even in relatively mild amidation procedures. , To achieve mild reaction conditions, we adapted the T3P ( n -propanephosphonic acid anhydride) coupling method published by Dunetz et al The authors showed that a mixture of EtOAc and pyridine at 0 °C yielded the lowest degree of racemization. Another advantage of T3P is that the side products formed in the coupling reactions are water-soluble and hence can be readily separated by extraction during work up.…”
Section: Resultsmentioning
confidence: 99%
“…Although phenylalanine is not known for its susceptibility to racemization, like e.g., phenylglycine containing peptides, literature shows that phenylalanine racemization can occur even in relatively mild amidation procedures. , To achieve mild reaction conditions, we adapted the T3P ( n -propanephosphonic acid anhydride) coupling method published by Dunetz et al The authors showed that a mixture of EtOAc and pyridine at 0 °C yielded the lowest degree of racemization. Another advantage of T3P is that the side products formed in the coupling reactions are water-soluble and hence can be readily separated by extraction during work up.…”
Section: Resultsmentioning
confidence: 99%
“…The Nα attack from the same amino acid or peptide could lead to the epimerisation product (Figure 4). The path B mechanism was regarded as the most predominant source of amino acid racemisation during peptide synthesis [12]. [13].…”
Section: Introductionmentioning
confidence: 99%